Pengaruh Beta Saham, Debt to Equity Ratio dan Return On Asset terhadap Return Saham (Studi Kasus pada Saham-Saham LQ45 Periode 2018 – 2019) - Indah Pratiwi; Wahid Wachyu Adi Winarto (Politeknik Negeri Bengkalis, 2021)
This study aims to analyze the effect of stock beta, DER and ROA on stock returns on LQ 45 Shares 2018-2019. The research sample consisted of 45 companies LQ 45. The research method used secondary data in the form of financial reports with purposive sampling technique. The results showed that simultaneously beta, DER and ROA had a significant effect on stock returns. Partially, the beta variable has a significant negative effect on stock returns, while the DER and ROA variables have a positive and significant effect on stock returns.